2013
DOI: 10.1186/1741-7015-11-200
|View full text |Cite
|
Sign up to set email alerts
|

So depression is an inflammatory disease, but where does the inflammation come from?

Abstract: BackgroundWe now know that depression is associated with a chronic, low-grade inflammatory response and activation of cell-mediated immunity, as well as activation of the compensatory anti-inflammatory reflex system. It is similarly accompanied by increased oxidative and nitrosative stress (O&NS), which contribute to neuroprogression in the disorder. The obvious question this poses is ‘what is the source of this chronic low-grade inflammation?’DiscussionThis review explores the role of inflammation and oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
772
3
15

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 1,160 publications
(808 citation statements)
references
References 243 publications
18
772
3
15
Order By: Relevance
“…Anxiety, worries about the future and the results of clinical treatment can significantly influence the quality of immune reactions, as documented in a study of patients with Gulf War Syndrome [18] . In numerous patients were found conditions such as increase of depression with subsequent higher riskof persisting chronic inflammatory problems and activation of compensatory anti-inflammatory reflex system (CIRS), which can be characterized as negative immunoregulatory process [19] . Permanent stress is often accompanied with inflammation is directly connected to the nutrition status, mainly to obesity.…”
Section: Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety, worries about the future and the results of clinical treatment can significantly influence the quality of immune reactions, as documented in a study of patients with Gulf War Syndrome [18] . In numerous patients were found conditions such as increase of depression with subsequent higher riskof persisting chronic inflammatory problems and activation of compensatory anti-inflammatory reflex system (CIRS), which can be characterized as negative immunoregulatory process [19] . Permanent stress is often accompanied with inflammation is directly connected to the nutrition status, mainly to obesity.…”
Section: Protocolmentioning
confidence: 99%
“…It is speculated that quality of diet and most of all regular psychical problems, depression and fatigue can help to negatively influence immune mechanisms [19] . Changes in adipose function, leptin levels, dysfunction of hypothalamic pituitary adenocorticoidal axes and oxidative stress play an important part in an inflammatory reaction of obese individuals.…”
Section: Protocolmentioning
confidence: 99%
“…There is now considerable evidence that acute psychotic, manic and depressive episodes are associated with abnormalities in a range of inflammatory markers, including elevation of proinflammatory cytokines (Frommberger et al 1997;Dickerson et al 2007;Goldstein et al 2011;Berk et al 2013;Khandaker et al 2015). There is also evidence that these disorders are longitudinally associated with previous inflammatory illnesses, for example maternal and childhood infections have been identified as risk factors for schizophrenia (Khandaker et al 2012(Khandaker et al , 2013 and bipolar disorder (Parboosing et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Recent meta-analyses summarize that depression is accompanied by mild systemic inflammation including increased levels of inflammatory cytokines, e.g. interleukin (IL)-6, IL-1 and tumor necrosis factor (TNF)α, and signs of an acute phase response [2,3]. Recently, a systematic review and a meta-analysis showed that antiinflammatory drugs may have antidepressant effects [4,5].…”
Section: Introductionmentioning
confidence: 99%